Structural and functional roles of carotenoids in chlorosomes - Pšencík, Jakub; Arellano, Juan B; Collins, Aaron M; Laurinmäki, Pasi; Torkkeli, Mika; Löflund, Benita; Serimaa, Ritva E; Blankenship, Robert E; Tuma, Roman; Butcher, Sarah J (Journal of bacteriology, 2013)
Chlorosomes are large light-harvesting complexes found in three phyla of anoxygenic photosynthetic bacteria. Chlorosomes are primarily composed of self-assembling pigment aggregates. In addition to the main pigment, bacteriochlorophyll c, d, or e, chlorosomes also contain variable amounts of carotenoids. Here, we use X-ray scattering and electron cryomicroscopy, complemented with absorption spectroscopy and pigment analysis, to compare the morphologies, structures, and pigment compositions of chlorosomes from Chloroflexus aurantiacus grown under two different light conditions and Chlorobaculum tepidum. High-purity chlorosomes from C. aurantiacus contain about 20% more carotenoid per bacteriochlorophyll c molecule when grown under low light than when grown under high light. This accentuates the light-harvesting function of carotenoids, in addition to their photoprotective role. The low-light chlorosomes are thicker due to the overall greater content of pigments and contain domains of lamellar aggregates. Experiments where carotenoids were selectively extracted from intact chlorosomes using hexane proved that they are located in the interlamellar space, as observed previously for species belonging to the phylum Chlorobi. A fraction of the carotenoids are localized in the baseplate, where they are bound differently and cannot be removed by hexane. In C. tepidum, carotenoids cannot be extracted by hexane even from the chlorosome interior. The chemical structure of the pigments in C. tepidum may lead to π-π interactions between carotenoids and bacteriochlorophylls, preventing carotenoid extraction. The results provide information about the nature of interactions between bacteriochlorophylls and carotenoids in the protein-free environment of the chlorosome interior.
Keywords: Phycobiliproteins; organely; molekulární struktura; světlo; Molecular Structure; biologické pigmenty; Bacterial Chromatophores; fykobiliproteiny; Organelles; Light; Chloroflexus; Pigments, Biological; Carotenoids; X-Ray Diffraction; difrakce rentgenového záření; bakteriální chromatofory; karotenoidy